تحديد العوامل المؤثرة على سلوك الاستهلاك العائلي في المملكة العربية السعودية - البسام، خالد عبدالرحمن حمد; البسام، تميم بن عبدالله (جامعة الملك عبد العزيز, 2021)
هدف هذه الدراسة هو التوصل إلى نموذج مقدر يفسر سلوك الاستهلاك العائلي في المملكة العربية السعودية، خلال الفترة من 1990 إلى 2018 م. ومن أجل تحليل سلوك الاستهلاك العائلي في المملكة العربية السعودية، تم في هذه الدراسة تحديد وتقدير نموذج لقياس العلاقة بين الاستهلاك العائلي من جهة وبعض المتغيرات الاقتصادية وغير الاقتصادية من جهة أخرى. بعد الاطلاع على فرضيات عدد من النظريات المتعلقة بالاستهلاك العائلي ونتائج عدد من الدراسات القياسية المتعلقة بالاستهلاك العائلي في الدول النامية والمملكة العربية السعودية بالإضافة إلى الأخذ في الاعتبار خصائص الاقتصاد السعودي، فإنه تم بناء نموذج قياسي يحوي على المتغيرات التفسيرية التالية: الدخل المحلي الإجمالي الحقيقي غير النفطي، وسلوك التضخم، والعامل الديموغرافي المتمثل بالنمو السكاني. أظهرت نتائج تقدير نموذج الدراسة على أن المتغيرات التفسيرية تفسر الجزء الأعظم من التغيرات في الاستهلاك العائلي في المملكة العربية السعودية.
The objective of this study is to specify a model that analyzes the behavior of household consumption in Saudi Arabian having been through the literature on household saving in Saudi Arabia. It is to our understanding that there been very few empirical studies, devoted to analyze empirically the behavior of household consumption. This means that this study will be an important contribution in this area. After reviewing a number of consumption theories and some important field studies on household consumption in Saudi Arabia and some developing and developed countries, an empirical model was determined to analyze the behavior of household consumption in Saudi Arabia. This model contained several explanatory variables that were expected to have a strong influence on the behavior of household consumption. These variables are real gross domestic income (real GDI), inflation, and finally the demographic variable (population growth). The estimated model of this study revealed that the estimated model’s explanatory variables are statistically significant.
Keywords: الاقتصاد القياسي -- الاستهلاك العائلي -- ثقافة الاستهلاك -- النمو السكاني -- السعودية